Communication with Health Personnel and Human Rights: A Perspective from People with Mental Disorders - Rojas-Andrade, R (Springer, 2024)
Mental health care has focused on participation, which, in addition to improving recovery processes, constitutes a tool to defend the human rights of people with mental disorders. For this participation, communication is a fundamental element. The objective of the present research was to analyzed the perception of the human rights and communication with healthcare personnel in care processes, from leaders of mutual aid groups or support groups in various contexts of Colombia. It is expected that the generated information can contribute to the evaluation of the quality of mental health services from a human rights and health participation perspective, in contexts similar to the one being analyzed. A qualitative approach has been used, which takes information from six leaders of support groups for mental health, in four regions of Colombia. Said information was analyzed through a thematic analysis, contrasting with the vision of the researchers and with the current theory. It is found that the subject of communication was made up of categories such as Previous ineffective treatments and Perception of a violation of dignity. Communication barriers are pointed out, such as attitudes of mental health professionals, but the influence that the health system and social and political barriers can have on the same communication is recognized. From the perception of leaders of mental health support groups, it is concluded that it is necessary to improve aspects of communication in health personnel. In addition, clinical mental health care could also be a space for the promotion of human rights. © The Author(s) 2024.
Keywords: Communication Barriers; Health Communication; Human Rights; Mental Health; Patient Rights; Physician–Patient Relations